The Role of Teaching Campus Program for Students in Increasing Competence at SD Negeri 57 Banda Aceh - Riadhil Jinan; Jalaluddin Jalaluddin; Zakaria Zakaria (Universitas Serambi Mekkah, 2022)
The concept of independent learning is an issue that is widely discussed in the world of education, the concept that voices the existence of independence in learning is carried out in an effort to prepare students who graduate from universities, both public and private, to be able to face the times and changes that occur so quickly. The Teaching Campus Program is one of the Programs of Merdeka Belajar Kampus Merdeka (MBKM) in the form of teaching assistance to empower students in assisting the learning process in elementary schools in various villages / cities, one of which is SD Negeri 57 Banda Aceh which is located in Jl. Lingkar kampus Unsyiah, Syiah Kuala District, Banda Aceh City, Aceh Province. In this program, students are responsible for assisting the school in the teaching process, assisting with technology adaptation, and assisting administration. In addition, students have a responsibility in improving students' Akhlaq and increasing students' motivation and interest in learning. The results of this program are expected to grow social sensitivity in students to help the surrounding community, hone thinking skills in working together both with teachers, and with students across fields of science in solving problems faced, developing students' insights, character and Soft Skills. Keywords: Education, teaching campus, elementary school.